Wellness Tourism Berbasis Kearifan Lokal: Strategi Pengembangan Pariwisata Pasca Covid-19 di Desa Bilebante, Nusa Tengara Barat - Midya Aulia Nisak; Siti Nurbayani; Siti Komariah (Department of Public Administration, Universitas Negeri Surabaya, 2022)
The purpose of this study is to describe the implementation of the concept of wellness tourism based on local wisdom in the management of the Bilebante Green Tourism Village (DWH) in West Nusa Tenggara Province after the COVID-19 pandemic. Pierre Bourdiu's habitus and structural functionalism theories are used as analytical frameworks. Responding to the negative impact of the COVID-19 pandemic on the tourism and economic sectors, DWH Bilebante managers have implemented the concept of wellness tourism based on local wisdom to increase tourism attractiveness and maintain people's sources of income. This research use a desciptive qualitative approach. Data collection techniques using interviews, observation, and documentation. Data sources involve village heads, tourism village heads, MSME actors, and village assistants. The results showed that the Bilebante Green Tourism Village could apply the concept of wellness tourism based on local wisdom. This can be seen from the development of sports tourism, the construction of fitness therapy infrastructure and certified training for therapists, the introduction of traditional medicine such as peretuk and sembek, as well as training programs for cultivating and processing herbal plants in a sustainable manner. In addition, there is synergy between managers and stakeholders.